COMPARISON OF ULTRASONOGRAPHY AND COMPUTED TOMOGRAPHY IN THE EVALUATION OF SUSPICIOUS OVARIAN MASSES (Journal of Pharmaceutical Negative Results, 2023)
Aim: The present study was undertaken to determine the role of US and CT in the evaluation of suspicious ovarian masses.Methods: This prospective observational study was carried out in the Department of Radiology for the period of 6 months. The study protocol was reviewed by the Ethical Committee of the Hospital and granted ethical clearance. Total 120 women were included as subjects in this prospective study.Results: Out of 120 patients, majority of patients belonged to 41-50 years of age group (42, 35%) followed by 31-40 years of age group (30, 25%). 18 patients (15%) belonged to 21-30 years and 51-60 age group <20 and >60 years of age group included 6 patients each. Mass abdomen was the most common presenting symptom and contributed to 40%. It is followed by pain abdomen of 25% and abdominal distension by 20%, others by pressure symptoms (10%), and loss of appetite (5%). Most common benign tumor is mucinous cystadenoma with a percentage of (55%) followed by serous cystadenoma (25%), others are Dermoid (10%), Fibro Thecoma (5%), Fibroma (2.5%), Granulose cell tumor (2.5%). Most common malignant tumour is papillary serous cystadeno carcinoma with a percentage of (35%) followed by mucinous cystadeno carcinoma (25%), others are serous cystadeno carcinoma (15%), papillary mucinous cystadeno carcinomoa (5%), Borderline Malignant (Serous – 5%, Mucinous – 10%), endometroid carcinoma (1.6%), Dysgerminoma (4.1%).Conclusion: In this present study showed significant differences in the two methods i.e USG and CT. CT is showing more advantages regarding tumor localization, characterization. Hence CT can be advised if the unusual abnormalities were observed in routine USG scan in the diagnosis of ovarian masses.